LA IMAGEN ESTEREOTIPADA DE LA MUJER EN LA POESÍA ÁRABE: TRADUCCIÓN Y ESTUDIO - Gogazeh, Ziyad Mohammad; Al-Afif, Ahmad Husein (European Scientific Journal, ESJ, 2015)
This article is regarded as ratification for the wrong vision that people in the West have about women in the Arab World. This vision is unfortunately has many mistakes because of the rumors and the bad impression that the western thinking have about Arabs and Islam. We tried in this article to provide some evidences from the Holy Koran and Al-Hadith of the Prophet Mohammad, in addition to some other evidences from the old Arabic poetry; these evidences show that women must be treated with great respect and honor.